The effect of coating of edible film from bovine split hide gelatin on beef meatballs properties - Wulandari, D.; Yuliatmo, R.; Sugiyanto, S. (Journal of the Indonesian Tropical Animal Agriculture, 2018)
The aim of research wasto determine the effect of the coating of edible film derived from bovine split hide gelatin on inhibiting microbiological damages and properties of the beef meatballs with different coating concentrations. The material used was gelatin types A (processed with acid curing agent) from the bovine split hide and glycerol. The completed randomize design (CRD) with a factorial pattern of 3 x 3 was used in this study. The first factor was 3 levels of coating concentration (0, 5, and 10%) and the second factor was 3 levels of storage time at 10oC (3, 6, and 9 days). It was continued to Duncan's Multiple Range Test (DMRT) if the treatment indicated significant effect at aprobability level of 5%.The results showed that the storage time and coating concentration affected the soluble protein, pH value, water holding capacity (WHC), and total plate count (TPC) in beef meatballs. Bovine split hide gelatin can be used as an edible coating on beef meatballs and extend the shelf time of beef meatballs.